Sherwin B. Nuland - Traverse, Lyn D. (The Hastings Center report, 2014)
Sherwin Nuland's contributions to the field of bioethics were many. In reaching the lay public, How We Die did much for end-of-life care, demythologizing the process of dying and helping doctors, patients, and families discuss death more honestly and openly. Ultimately, Shep taught me as much about life as he did about death.